UKURAN KAP MEMODERASI PENGARUH FINANCIAL DISTRESS DAN UKURAN PERUSAHAAN KLIEN PADA AUDIT REPORT LAG - Sugita, Krismayanti; Dwirandra, Anak Agung Ngurah Bagus (E-Jurnal Akuntansi, 2017)
The purpose of this study  was to examine  whether there is any influence between  financial distress and the size of the  company's clients on audit report lag  with firm size as a moderating. The  sample used in this study is a mining company listed on the   Indonesia Stock Exchange with a span of   years   from 2013  to  2015. The  sample  selection  using  purposive sampling method. Data analysis technique used is the  logistic regression analysis  for  hypothesis 1   and  2, and  Moderated  Regression  Analysis (MRA) for hypothesis 3 and 4. The results of the analysis showed that the negative impact  of  financial  distress on the audit report lag. The size of the client  companies have   negative   effect on the audit report lag. Firm size is not able to   strengthen or weaken the   effect of financial distress and the size of the company's clients on audit report lag.
Keywords: Audit Report Lag, Financial Distress, Company Size Clients, Firm Size